Preparation of polypyrrole nanobowls and their effect for improving direct current dielectric properties of polyethylene. (September 2016) - Zhang, Chengcheng; Li, Yafeng; Li, Chunyang; Duan, Sixu; Yang, Jiaming; Han, Baozhong
Abstract: Polypyrrole (PPy) nanobowls were successfully prepared through a reactive self-degraded template polymerization and the morphology of PPy nanobowls was characterized by scanning electron microscopy (SEM). The nanobowls were uniform with diameters of about 100 nm. The low density polyethylene/polypyrrole (LDPE/PPy) nanocomposites were obtained by melt blending method. The structures of PPy nanobowls and the nanocomposites were studied by Fourier transform infrared spectrometer (FTIR). Space charge distributions in LDPE/PPy nanocomposites with different PPy nanobowls contents were measured using the pulsed electroacoustic (PEA) method. The results indicated that PPy nanobowls doping with a small quantity exhibited excellent suppression performance of space charge accumulation in LDPE and the nanocomposites showed improved direct current (DC) electrical conductivity and breakdown characteristics.